2020
DOI: 10.21203/rs.3.rs-17366/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

MicroRNA-19b-3p suppresses gastric cancer development by negatively regulating Neuropilin-1

Abstract: Background Gastric cancer (GC) remains one of the most common digestive malignancies worldwide and ranked third causes of cancer-related death. Mounting evidence has revealed that miRNAs exert critical regulatory roles in GC development. Methods Immunohistochemistry (IHC) and western blot assay were performed to determine the protein expression levels of neuropilin-1 (NRP1) and mRNA levels were confirmed by quantitative RT-PCR (qRT-PCR) in GC tissues. Kaplan–Meier analysis was performed to evaluate the prognos… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
1
2
0
Order By: Relevance
“…As reported in gastric cancer, miR-19b-3p was downregulated and negatively regulated neuropilin-1 [33]. In this study, through bioinformatics prediction and luciferase reporter and pull-down assay, RAB14 was found to be a potential target gene of miR-19b-3p.…”
Section: Discussionsupporting
confidence: 59%
“…As reported in gastric cancer, miR-19b-3p was downregulated and negatively regulated neuropilin-1 [33]. In this study, through bioinformatics prediction and luciferase reporter and pull-down assay, RAB14 was found to be a potential target gene of miR-19b-3p.…”
Section: Discussionsupporting
confidence: 59%
“…Thus, the ARGs signature-based prognostic nomogram was highly recommended for future clinical applications. Previous studies had demonstrated the influence of angiogenesis on tumor growth and progression (Katayama et al 2019;Carmeliet and Jain 2000;Ramjiawan et al 2017;Pavlakovic et al 2001;Schmidt and Carmeliet 2011;Baselga et al 2008;Goos et al 2016;Sbiera et al 2017;Wei et al 2020;Dunne et al 2006;Townsend et al 2019;Javaherian and Lee 2011;Lin et al 2003;Maurer et al 2006;Yang et al 2020). Moreover, inhibiting angiogenesis has emerged as an effective therapeutic strategy for most solid tumors.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 This abnormal miRNA expression has been reported in a variety of cancers, 7,8 such as colorectal cancer, 9 oral cancer, 10 breast cancer, 11 and bladder cancer. 12 Unusual miR-19b expression has been reported in gastric cancer, 13 lung cancer, 14 and breast cancer. 15 In colon cancer, Zhang reported that miR-19b upregulation was associated with metastasis and poor prognosis.…”
Section: Introductionmentioning
confidence: 99%